ANALYSIS OF SERVICESCAPE AND PRICE COMPETITION ON CUSTOMER LOYALTY THROUGH CUSTOMER ENGAGAMENT AT TRADITIONAL COFFEE SHOPS IN MEDAN CITY - Pane, Hartini Pratiwi; Endang Sulistya Rini; Beby Karina Fawzeea Sembiring (DAS CONFERENCE INTERNATIONAL SERIES, 2025)
The purpose of this study is to determine directly and indirectly the relationship between servicescape and price competition on customer loyalty through customer experience at traditional coffe sjops in Medan City. The population in this study is all consumers of traditional coffee shops in Medan City, with a number that cannot be known with certainty. The research sample was taken using the Zikmund formula so that a sample size of 100 respondents was obtained. Data analysis was carried out using structural equation modeling (SEM) techniques with Smart-PLS analysis tools to test the direct and indirect relationships between these variables. The results explain that servicescape directly has a significant effect on customer engagement, price competition directly has a significant effect on customer engagement, servicescape directly has a significant effect on customer loyalty, price competition directly has a significant effect on customer loyalty, customer engagement directly has a significant effect on customer loyalty, servicescape indirectly has a significant effect on customer loyalty through customer engagement and then price competition indirectly has a significant effect on customer loyalty through customer engagement